Planets to cosmology : essential science in the final years of the Hubble Space Telescope : proceedings of the Space Telescope Science Institute Symposium, held in Baltimore, Maryland, May 3-6, 2004 - Space Telescope Science Institute (U.S.). Symposium (2004 : Baltimore, Md.); Livio, Mario, 1945-; Casertano, Stefano; Space Telescope Science Institute (U.S.) (Cambridge ; New York : Cambridge University Press, 2006)
This 2006 book acknowledges the importance of identifying the most crucial science to be performed by the superb Hubble Telescope. With this goal in mind, the book presents a review of some of the most important open questions in astronomy. World experts examine topics ranging from extrasolar planets and star formation to supermassive black holes and the reionization of the universe. Special emphasis is placed on what astronomical observations should be carried out during the next few years to enable breakthroughs in our understanding of a complex and dynamic universe. In particular, the reviewers attempt to identify those topics to which the Hubble Space Telescope can uniquely contribute. The special emphasis on future research makes this book an essential resource for both professional researchers and graduate students in astronomy and astrophysics.
Preface -- Hubble's view of transiting planets / D. Charbonneau -- Unsolved problems in star formation / C.J. Clarke -- Star formation in clusters S.S. Larson -- HST abundance studies of low metallicity stars / J.W. Truran, C. Sneden, F. Primas, J.J. Cowan, and T. Beers -- Physical environments and feedback: HST studies of intense star-forming environments / J.S. Gallagher, L.J. Smith, and R.W. O'Connell -- Quasar hosts: growing up with monstrous middles / K.K. McLeod -- Reverberation mapping of active galactic nuclei / B.M. Peterson and K. Horne -- Feedback at high redshift / A.E. Shapley -- The baryon content of the local intergalactic medium / J.T. Stocke, J.M. Shull, and S.V. Penton -- Hot baryons in supercluster filaments / E.D. Miller, R.A. Dupke, and J.N. Bregman -- Galaxy assembly / E.F. Bell -- Probing the reionization history of the Universe / Z. Haiman -- Studying distant infrared-luminous galaxies with Spitzer and Hubble / C. Papovich, E. Egami, E. Le Floc'h, P. Pe;rez-González, G. Rieke, J. Rigby, H. Dole, and M. Reike -- Galaxies at z = g-i'-drop selection and the GLARE Project / E.R. Stanway, K. Glazebrook, A.J. Bunker, and the GLARE Consortium -- The Hubble Ultra Deep Field with NIMCOS / R.I. Thompson, R.J. Bouwens, and G. Illingworth.
"Published for the Space Telescope Science Institute."
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Hubble Space Telescope (Spacecraft); Hubble Space Telescope (Spacecraft); Astronomy -- Research -- Congresses; Space telescopes -- Research -- Congresses; Astronomie -- Recherche -- Congrès.; Télescopes spatiaux -- Recherche -- Congrès.; SCIENCE -- Astronomy; Astronomy -- Research; Planets; Hubble Space Telescope; Planets; Cosmology; Conference papers and proceedings